Locus of Control and Its Influence on Generation Z’s Financial Management in Malang - Meda Shava Navilla; ⁠Sumiati ⁠Sumiati; Himmiyatul Amanah Jiwa Juwita (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This research investigates the effects of financial attitude, income, and financial knowledge on personal financial management (PFM) among Generation Z in Malang City, incorporating locus of control as a mediating factor. Utilizing a quantitative method, the study collected data from 325 Generation Z respondents through a survey and employed Structural Equation Modeling with Partial Least Squares (SEM-PLS) using SmartPLS software for analysis. The findings indicate that financial knowledge significantly and positively influences PFM, both directly and indirectly through the mediation of locus of control. In contrast, financial attitude does not exert a direct influence on PFM, though it significantly impacts locus of control. Income is found to have no significant effect on PFM, either directly or indirectly. These results underscore the importance of financial literacy and an individual’s internal belief in managing financial outcomes as key drivers of effective financial behavior among Generation Z. The study offers theoretical contributions by advancing the Theory of Planned Behavior and provides practical insights for educational and financial institutions to improve financial knowledge and strengthen internal control perceptions. Enhancing these elements may support Generation Z in achieving stronger financial security and long-term economic well-being.